Novel angiotensin-converting enzyme inhibitory peptides from tuna byproducts—milts: Preparation, characterization, molecular docking study, and antioxidant function on H2O2-damaged human umbilical vein endothelial cells - Suo, Shi-Kun; Zheng, Shuo-Lei; Chi, Chang-Feng; Luo, Hong-Yu; Wang, Bin (Frontiers in Nutrition, 2022)
To prepare peptides with high angiotensin converting enzyme (ACE) inhibitory (ACEi) activity, Alcalase was screened from five proteases and employed to prepare protein hydrolysate (TMH) of skipjack tuna (Katsuwonus pelamis) milts. Subsequently, ten novel ACEi peptides were isolated from the high ACEi TMH and identified as Tyr-Asp-Asp (YDD), Thr-Arg-Glu (TRE), Arg-Asp-Tyr (RDY), Thr-Glu-Arg-Met (TERM), Asp-Arg-Arg-Tyr-Gly (DRRYG), Ile-Cys-Tyr (ICY), Leu-Ser-Phe-Arg (LSFR), Gly-Val-Arg-Phe (GVRF), Lys-Leu-Tyr-Ala-Leu-Phe (KLYALF), and Ile-Tyr-Ser-Pro (IYSP) with molecular weights of 411.35, 404.41, 452.45, 535.60, 665.69, 397.48, 521.61, 477.55, 753.91, and 478.53 Da, respectively. Among them, the IC50 values of ICY, LSFR, and IYSP on ACE were 0.48, 0.59, and 0.76 mg/mL, respectively. The significant ACEi activity of ICY, LSFR, and IYSP with the affinity of -7.0, -8.5, and -8.3 kcal/mol mainly attributed to effectively combining with the ACEi active sites through hydrogen bonding, electrostatic force and hydrophobic interaction. Moreover, ICY, LSFR, and IYSP could positively influence the production of nitric oxide (NO) and endothelin-1 (ET-1) secretion in human umbilical vein endothelial cells (HUVECs), and weaken the adverse impact of norepinephrine (NE) on the production of NO and ET-1. In addition, ICY, LSFR, and IYSP could provide significant protection to HUVECs against H2O2 damage by increasing antioxidase levels to decrease the contents of reactive oxide species and malondialdehyde. Therefore, the ACEi peptides of ICY, LSFR, and IYSP are beneficial functional molecules for healthy foods against hypertension and cardiovascular diseases.